(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2020)
This article reflects on the relationship between two concepts: object and memory. It approaches the object not only from the manipulation but from the link that is established with the subject when she is an activator of memories. The object is approached from its autonomy and in relation to the artist who works with it. The object as a bearer of memories is analyzed in that liminal zone between theater of objects and performance. This reflection is accompanied by the thoughts of artists/researchers, among which Violeta Luna, Ana Amaral and Ana Alvarado stand out. The approach is carried out from the perspective of an immigrant granddaughter, as the bearer of disputed memories.